Demonstration of antigenic and specific surface association heat shock protein(s) of acinetobacter baumannii - Hasnur, Nur Nadhra Adila (2018)
Acinetobacter baumannii is an important nosocomial pathogen associated with high mortality. It is a major concern of hospital acquired infection (HAI) worldwide. Until recently, the resistance of Acinetobacter baumannii has increased steadily against all first-line antibiotics. Due to this situation, the choice of antimicrobial agents to treat Acinetobacter baumannii infections is limited. Currently, the gold standard method for identification of Acinetobacter species is the DNA-DNA hybridization while the two recommended methods that are widely accepted for identification of Acinetobacter species are amplified rDNA restriction analysis (ARDRA) and amplified fragment length polymorphism (ALFP). However, these methods are too laborious for everyday diagnostic use. Thus, there is a need to develop an early detection of Acinetobacter baumannii to reduce the time consuming in detecting the infection in patients. Development of a specific and sensitive diagnostic test requires discovery of biomarker(s) which does not cross react with other bacteria and specific only to Acinetobacter baumannii. Heat shock proteins (HSP) are proteins that expressed in bacteria during stress environment and these proteins have potential as biomarker in diagnostic field. Thus, the aim of this study is to detect the presence of HSPs and biomarker(s) in the surface associated proteins (SAPs) of Acinetobacter baumannii. The SAPs profile from the ATCC 19606 strain and clinical isolate of Acinetobacter baumannii were demonstrated using Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE). This study demonstrated that the expression level ofSAPs of Acinetobacter baumannii varies with increasing temperature. The SAPs profiles expressed at 37°C was compared with 38.5°C and 41°C to assess the effect of temperatures on the expression of the SAPs. The protein was subjected to Western blot using serum from patients infected with Acinetobacter baumannii as well other bacteremia infections. Result of this study demonstrated various antigenic bands detected when probed with sera from patients with Acinetobacter baumannii infections (incubated at 37°C and 41°C) against IgA, IgM and IgG isotypes. All the antigenic bands were checked for cross reaction using sera from patients infected with Enterococcus faecalis, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella spp, Staphylococcus aureus, Enterococcus faecalis and methicillin-resistant Staphylococcus aureus (MRSA). Five specific and antigenic proteins were selected for further identification by MALDI-ToF analysis. The protein 96.7kDa, 62.0kDa, 37.9kDa, 25.0kDa and 16.0kDa from Acinetobacter baumannii were identified as catalase HPII, Hsp60 chaperonin, phosphate ABC transporter substrate binding protein, Ycei-like protein, and Lipopolysaccharide export system protein LptA, respectively. The increased expression of antigenicity level of these proteins probably is a survival mechanism of the bacteria at higher temperature in the host body and could be potential diagnostic biomarkers for diagnostic and vaccine development.